Evaluation of Superconducting Magnet Shield Configurations for Long Duration Manned Space Missions - Ambroglini, Filippo; Battiston, Roberto; Burger, William J. (Frontiers in Oncology, 2016)
A manned mission to Mars would present an important long term health risk to the crew members due to the prolonged exposure to the ionizing radiation of galactic cosmic-rays. The radiation levels would largely exceed those encountered in the Apollo missions. An increase in the passive shielding provided by the spacecraft implies a significant increase of the mass. The advent of superconducting magnets in the early 1960's was considered an attractive alternative. The technology allows to generate magnetic fields capable to deflect the cosmic-rays in a manner analogous to the reduction of the particle fluxes in the upper atmosphere, due to the Earth's dipole magnetic field. \newline\newline A series of the three studies have been conducted over the last five years, funded successively by European Space Agency~(ESA), the NASA Innovative Advanced Concepts~(NIAC) program and the Union European's Seventh Framework Programme~(FP7). The shielding configurations studied are based on high temperature superconductors, which eliminate the need to operate with liquid helium. The mass estimates of the coils and supporting structure of the engineering designs are based on the current and expected near-future performance of the superconducting materials. In each case, the shield performance, in terms of dose reduction, is provided by a 3-dimensional Monte Carlo simulation, which treats in detail the electromagnetic and hadronic interactions of the galactic-cosmic rays, and the secondary particles they produce in the materials of the shield and spacecraft. A summary of the results of the studies, representing one of the most detailed and comprehensive efforts made in the field, is presented.